Discussion on standard and robust Kalman filters, using post-earthquake data set of 17 August 1999 Izmit earthquake - Dogan, U; Ergintav, S; Demirel, H (TAYLOR & FRANCIS LTD, 2003)
We discuss on the performances of standard and robust Kalman filters to estimate the post-seismic deformation field produced by the 17 August 1999 Izmit, Turkey, earthquake. The data set covers a subset of the Marmara Continuous GPS (Global Positioning System) Network (MAGNET) and other available survey stations in the region. The results of the models suggest that the standard Kalman filter estimate is not optimal due to serious bias that occurs between epochs. The bias, however, can be detected and removed using a robust Kalman filter.
Keywords: POSTSEISMIC DEFORMATION; DUZCE; TURKEY; GPS; Engineering; Geology; Remote Sensing